Systematic Discrimination in School Exclusions and Pathways to Youth Justice: Insights from Linked Education and Justice Data in England - Chobhthaigh, Sorcha Ní; Cox, Camille; Greenway-Bailey, Twyla; Musanu, Josephine; Devakumar, Delan; Jay, Matthew (International Journal of Population Data Science, 2026)
School exclusions represent harmful disciplinary responses to emotional, behavioural or relational needs that increase risks of escalation, educational disengagement, and justice system involvement. Racial-ethnic and gender inequalities in school responses to mental health needs perpetuate inequalities in health, education and justice outcomes. Developed in partnership with peer researchers and community stakeholders, we examined systematic differences between exclusions, Special Educational Needs and Disability (SEND) for Social, Emotional and Mental Health (SEMH) needs and juvenile justice contacts, based on gender and racial-ethnic group. We examined rates, timing and risk ratios of exclusions in relation to SEND-for-SEMH and juvenile justice contacts using national linked education and justice system data for 3.7m children (born 1997-2003) attending state schools in England aged 5-16. Boys from Mixed white-Black, Mixed Other, Black, Pakistani, Bangladeshi, Romani, and Irish Traveller backgrounds, plus Mixed white-Black Caribbean, Black Caribbean, and Romani girls, were significantly more likely to be excluded before/without receiving SEND-for-SEMH. Most girls and pupils from Asian, Black African, Black Other, white Other, Mixed white-Asian, Mixed Other and Other racial-ethnic group backgrounds were significantly less likely to receive SEND-for-SEMH following exclusions. Among those excluded first, boys from white Irish, Mixed race/ethnicity, Black Caribbean, Black Other, Romani and Irish Traveller backgrounds faced significantly elevated risk of juvenile justice contacts. Linked data reveals how systematic discrimination in school responses fuels the cycle of unmet mental health need and justice involvement. Reducing inequalities in health, education and youth justice requires co-ordinated integration across systems and equitable access to mental health care.